2022
DOI: 10.21203/rs.3.rs-1935194/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic ultrasound ameliorates pulmonary fibrosis through inhibiting TGF-β/SMAD-mediated epithelial mesenchymal transition

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a progressive pulmonary interstitial inflammatory disease with no effective treatment. Lung epithelial injury and dysfunction are the core of initiating the pathogenic process. Following injury to the lung epithelium, inflammatory cell recruitment, fibroblast proliferation and extracellular matrix expansion ultimately lead to tissue fibrosis. Chronic inflammatory microenvironment is closely related to the development of epithelial mesenchymal transition (EMT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A patent filed regarding the role of apigenin stated that it can both inhibit and invert the development of EMT process. Indeed, cells treated with apigenin present a decreased expression of mesenchymal marker and epithelial markers in a dose-dependent manner [86]. Similarly, another patent demonstrated that irradiated apigenin has more therapeutic potential in treating lung cancer cells as compared to the non-irradiated apigenin.…”
Section: The Therapeutic Potential Of Apigenin In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A patent filed regarding the role of apigenin stated that it can both inhibit and invert the development of EMT process. Indeed, cells treated with apigenin present a decreased expression of mesenchymal marker and epithelial markers in a dose-dependent manner [86]. Similarly, another patent demonstrated that irradiated apigenin has more therapeutic potential in treating lung cancer cells as compared to the non-irradiated apigenin.…”
Section: The Therapeutic Potential Of Apigenin In Cancer Treatmentmentioning
confidence: 99%
“…The pharmaceutical composition directly induced apoptosis in lung cancer cells thus preventing tumor growth, while facilitates chemoprevention. Briefly, it reduced the rate of glycolysis, ATP production, while downregulated ANT2 and suppressed PD-L1 [84]. Also, it has been reported that apigenin can modulate the epithelial to mesenchymal transition (EMT) [85].…”
Section: The Therapeutic Potential Of Apigenin In Cancer Treatmentmentioning
confidence: 99%